KEHIDUPAN DOSEN DI UNIVERSITAS TERBUKA DALAM PERSPEKTIF DOSEN PEREMPUAN DENGAN ANAK - udini, Syams (Pusat Studi Gender dan Anak LPPM UIN Sunan Ampel Surabaya, 2013)
Historically,Â Â public and domestic area can not pair harmoniously. The potential conflict is even greater forwomen with have children . This condition leads to have less opprotuinities in terms of job compared to men.The separation between public and domestic spheres is due to social norms that perceive work and family asdifferent areas. In fact, this separation also is used against women and force them to stop working when theywere pregnant. Actually, gender difference is not a problem as far as not causing gender discrimination.Unfortunately, there are many problems caused relaed to gender differences. There are many challenges thatmust be faced by women to be able to enggage in the public domain, moreover to be able to keep the balancebetween the personal and career lifeÂ .